2009
DOI: 10.1371/journal.ppat.1000364
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Roles for FOXP3+ and FOXP3− CD4+ T Cells in Regulating Cellular Immunity to Uncomplicated and Severe Plasmodium falciparum Malaria

Abstract: Failure to establish an appropriate balance between pro- and anti-inflammatory immune responses is believed to contribute to pathogenesis of severe malaria. To determine whether this balance is maintained by classical regulatory T cells (CD4+ FOXP3+ CD127−/low; Tregs) we compared cellular responses between Gambian children (n = 124) with severe Plasmodium falciparum malaria or uncomplicated malaria infections. Although no significant differences in Treg numbers or function were observed between the groups, Tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
224
3
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 198 publications
(259 citation statements)
references
References 75 publications
25
224
3
6
Order By: Relevance
“…Epidemiological studies suggest that repeatedly exposed individuals eventually develop protective immunity (such that adults in endemic areas rarely develop CM), which may be characterized by the ability to control parasite replication (keeping parasite densities below the critical threshold for induction of inflammation or impairment of cerebral blood flow), to prevent pRBC sequestration or to regulate the inflammatory process (ArtavanisTsakonas et al 2003 ;Walther et al 2009). …”
Section: Human Cerebral Malariamentioning
confidence: 99%
“…Epidemiological studies suggest that repeatedly exposed individuals eventually develop protective immunity (such that adults in endemic areas rarely develop CM), which may be characterized by the ability to control parasite replication (keeping parasite densities below the critical threshold for induction of inflammation or impairment of cerebral blood flow), to prevent pRBC sequestration or to regulate the inflammatory process (ArtavanisTsakonas et al 2003 ;Walther et al 2009). …”
Section: Human Cerebral Malariamentioning
confidence: 99%
“…Recent studies show that T regs can modify susceptibility to disease (77,78) and contribute to whether the host immune responses are protective or pathological in response to infection with P. falciparum parasites (73,(79)(80)(81)(82). The nature of the initial exposure to malaria Ags likely affects the potentially diverse roles assumed by T regs in malaria infection.…”
Section: Cd25mentioning
confidence: 99%
“…As for conventional T cells, it has been shown that the majority of CD4 T cells with regard to the expression of CCR and apoptotic molecules and suggest that CD25, rather than being a marker of Treg per se, is a marker of activated Treg. Given our interest in Treg function during malaria infection [38,[44][45][46][47], we further aimed to study these markers in relation to Treg activation status in vitro, using Plasmodium falciparum schizont extract (PfSE). Importantly, we show that -irrespective of the culture conditions -the phenotype of FOXP3 1 T cells is modified when they are kept in in vitro culture, affecting both expression of CCR and molecules involved in apoptosis, indicating a need for caution when comparing data from in vitro and ex vivo studies.…”
Section: Foxp3mentioning
confidence: 99%